2015
DOI: 10.1631/jzus.b1400370
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and root glucosinolate profiles of Chinese cabbage (Brassica rapa ssp. pekinensis) as a systemic response to methyl jasmonate and salicylic acid elicitation

Abstract: Zang et al. / J Zhejiang Univ-Sci B (Biomed & Biotechnol) 2015 16(8)Abstract: Glucosinolates (GSs) are an important group of defensive phytochemicals mainly found in Brassicaceae. Plant hormones jasmonic acid (JA) and salicylic acid (SA) are major regulators of plant response to pathogen attack. However, there is little information about the interactive effect of both elicitors on inducing GS biosynthesis in Chinese cabbage (Brassica rapa ssp. pekinensis). In this study, we applied different concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In Brassica rapa , SA antagonistically affected methyl-JA induced GLS accumulation in the root regardless of the site of elicitation. Similar effect was found in the leaves when the roots were elicited, however, the effect was synergetic if the leaves were elicited ( Zang et al, 2015 ).…”
Section: Regulation Of Gls Biosynthesismentioning
confidence: 58%
“…In Brassica rapa , SA antagonistically affected methyl-JA induced GLS accumulation in the root regardless of the site of elicitation. Similar effect was found in the leaves when the roots were elicited, however, the effect was synergetic if the leaves were elicited ( Zang et al, 2015 ).…”
Section: Regulation Of Gls Biosynthesismentioning
confidence: 58%
“…In fact, the levels of total glucosinolates found in 63 varieties of B. rapa from northwestern Spain evaluated at two different sites (Padilla et al 2007) were lower (34.5 and 26 lmol/g DW) than those found in B. rapa hairy root cultures elicited with 50 lM jasmonic acid (about 75 lmol/g DW, Kastell et al 2013a). Similarly, Zang et al (2015) showed that the maximal levels of total glucosinolates found in leaves of B. rapa ssp. Pekinensis elicited with 200 lM of methyl jasmonate were 62.12 ± 5.56 lmol/g DW while the levels found in roots were higher (114.05 lmol/g DW).…”
Section: The Addition Of Elicitors To Improve the Bioproduction Of Glmentioning
confidence: 90%
“…However, transgenic hairy root cultures which overexpressed CYP79B2 and CYP83B1 or CYP83B1, CYP79B2 and CYP79B3 accumulated high levels of 4-methoxy glucobrassicin (about 1.17 and 0.95 nmol/g FW, respectively) compared to non-transgenic hairy root cultures (0.5 nmol/g FW) ( Table 2). Another transgenic line transformed with CYP79B2, CYP79B3 and CYP83B1 genes also showed an increase in the levels of glucobrassicin being 1.5-fold greater than control lines (Zang et al 2009). Kastell et al (2015) also observed high levels of short-chain aliphatic and indole glucosinolates (about 3.5 and 9 lmol/g DW, respectively) in A. thaliana hairy root cultures with an additional expression of CYP79F1 (Table 2).…”
Section: Metabolic Engineering As Strategy To Enhance the Biosynthesimentioning
confidence: 91%
“…Exogenous application of jasmonic acid (JA) or salicylic acid (SA) is often used to mimic biotic stress. In notable number of studies, JA and SA applications have been shown to increase accumulation of beneficial biomolecules, including glucosinolates [21,22,23,24,25,26,27,28,29,30,31,32,33]. Methyl jasmonate (MeJA) can be utilized in fields for Brassica vegetable production to enhance human health-promoting glucosinolates and the market value of the products [25].…”
Section: Introductionmentioning
confidence: 99%